2004
DOI: 10.1016/j.bbadis.2003.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Liver necrosis and fulminant hepatic failure in rats: protection by oxyanionic form of tungsten

Abstract: The hepatic lesion produced as a result of oxidative stress is of wide occurrence. In the present study, the effect of tungsten on liver necrosis and fulminant hepatic failure (FHF) has been studied in rats treated with various compounds known to produce oxidative stress. Supplementation of animals with sodium tungstate for 7 weeks before the induction of liver injury by chemicals including thioacetamide (TAA), carbon tetrachloride (CCl(4)), or chloroform (CHCl(3)) could protect progression of hepatic injury. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 42 publications
1
28
0
1
Order By: Relevance
“…TAA generates liver damage by upregulating hepatic XO activity [2]. This feature of TAA makes it a proper hepatotoxic agent for testing the effects of XO inhibition [3]. Therefore inhibition of XO may be a logical approach for prevention of tissue damage resulting from XO-derived ROS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TAA generates liver damage by upregulating hepatic XO activity [2]. This feature of TAA makes it a proper hepatotoxic agent for testing the effects of XO inhibition [3]. Therefore inhibition of XO may be a logical approach for prevention of tissue damage resulting from XO-derived ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Despite technological advances and improvement in intensive care conditions, ALF continues to be one of the most challenging problems in clinical practice [1]. In various liver injury models [2][3][4][5], it has been revealed that increased xanthine oxidase (XO) activity plays pivotal role in the oxidative stress-induced hepatic damage. XO is widely distributed throughout various tissues with the highest level in the liver [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28) Many studies demonstrated that tungstate has effects on the anti-diabetes, 29,30) hepatoprotection, 22,31) and various beneficial actions.…”
mentioning
confidence: 99%
“…27,28) Many studies demonstrated that tungstate has effects on the anti-diabetes, 29,30) hepatoprotection, 22,31) and various beneficial actions. 32,33) Furthermore, it was well known that XO activity was decreased by tungstate via replacement of molybdenum in enzyme molecule.…”
mentioning
confidence: 99%